1984
DOI: 10.1007/bf00177901
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral autologous mononuclear cells in the treatment of recurrent glioblastoma multiforme

Abstract: Four patients with malignant gliomas recurring after surgical resection, radiotherapy and chemotherapy were entered into a trial of immunotherapy. Partial removal of the recurrent tumors was performed and autologous mononuclear cell infusions were given into the resection cavity via a subgaleal reservoir that had been inserted at the time of tumor resection. Mononuclear cells were obtained using a cell separator and Ficoll-hypaque separation techniques. Patients were followed carefully with clinical examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Early studies utilized peripheral blood mononuclear cells (PBMCs), lymphokineactivated killer cells, consisting of IL-2-activated PBMCs, and tumor-infiltrating lymphocytes (TILs), and administered cells into the tumor cavity after resection. Most patients did not experience any adverse events, but there was also no significant impact on outcomes [59][60][61]. One novel cell-based strategy that has been successful is the transduction of T-cells with T-cell receptor signaling molecules and chimeric antigen receptors (CARs) that recognize TSAs.…”
Section: Peptide and DC Vaccination And T-cell Transfer Therapymentioning
confidence: 99%
“…Early studies utilized peripheral blood mononuclear cells (PBMCs), lymphokineactivated killer cells, consisting of IL-2-activated PBMCs, and tumor-infiltrating lymphocytes (TILs), and administered cells into the tumor cavity after resection. Most patients did not experience any adverse events, but there was also no significant impact on outcomes [59][60][61]. One novel cell-based strategy that has been successful is the transduction of T-cells with T-cell receptor signaling molecules and chimeric antigen receptors (CARs) that recognize TSAs.…”
Section: Peptide and DC Vaccination And T-cell Transfer Therapymentioning
confidence: 99%
“…In the past decade, different cell types have been studied to best induce antitumor immunity in tumor bearing hosts. Different cell types that have been used include (i) peripheral blood mononuclear cells (PBMCs) or peripheral blood lymphocytes (PBL) [148,149], (ii) lymphokine-activated killer cells (LAKS) [150][151][152], (iii) mitogen-activated killer cells (MAKs) [153,154], (iv) tumor infiltrating lymphocytes (TILs) [155], and (v) antigen specific cytotoxic lymphocytes [156,157]. In 1992, Riddell et al [158] reported that the adoptive transfer of T cell clones restored viral immunity in patients undergoing hematopoietic stem cell transplant.…”
Section: Adoptive Cell Transfermentioning
confidence: 99%
“…Adoptive cell transfer was first studied in hematopoietic stem cell transplant in a non-myeloablative setting used for the treatment of chronic myeloid leukemia [160] and was further developed for solid tumors. In 1984, Steinbok et al [148] was the first to demonstrate the safety and feasibility if adoptive immunotherapy for brain malignancies, but saw no measurable benefit to patient outcome. This landmark study was based on previous observations that GBM patients had observed lymphocytic infiltrates at tumor sites [148], suggesting that there was an attempt to mount an immune response by endogenous immune cells [161,162].…”
Section: Adoptive Cell Transfermentioning
confidence: 99%
See 2 more Smart Citations